6. Lower limb strength and associated factors among older patients with dementia - Luc, Tran Viet; Anh, Nguyen Trung; Huong, Nguyen Thi Thu (Tạp chí Nghiên cứu Y học, 2024)
This cross-sectional study was conducted to assess lower limb strength and related factors among older people with dementia examined and treated at the National Geriatric Hospital. Lower limb strength was assessed using the 30-Second Chair Stand Test. The proportion of participants with impaired lower limb strength was 78.2%. There were significant associations between impaired lower limb strength and diabetic patients. There were significant associations between impaired lower limb strength and geriatric syndromes: malnutrition, high risk of falls, and dependence or partial dependence according to the Barthel Index. There was no significant difference between the type of dementia and the level of dementia with impaired lower limb strength. In conclusion: Three-quarters of older dementia patients have impaired lower limb strength. Our results highlighted that diabetes, and geriatric syndromes such as malnutrition, high fall risk, dependence, and partial dependence were significantly associated with lower limb strength in older patients with dementia.